New biological and chemical evidences of two lamiaceae species (thymbra capitata and thymus sipyleus subsp. rosulans): In vitro, in silico and ex vivo approaches - EMRE, GİZEM (My University, 2022)
In this study, the methanolic and infusion extracts of two species, Thymbra capitata and Thymus sipyleus subsp. rosulans, were tested for their chemical composition and biological abilities (antioxidant, enzyme inhibitory and anti-inflammatory effects). The extracts yielded total phenolic and flavonoid contents in the range of 83.43-127.52 mg GAE/g and 9.41-46.34 mg RE/g, respectively. HPLC analysis revealed rosmarinic acid to be a major component of the studied extracts (15.85-26.43%). The best ABTS radical scavenging ability was observed in the methanol extract of T. capitata with 379.11 mg TE/g, followed by in the methanol extract of T. sipylus (360.93 mg TE/g). In the CUPRAC assay, the highest reducing ability was also found in the methanol extract of T. capitata with 802.22 mg TE/g. The phosphomolybdenum ability ranged from 2.39 to 3.61 mmol TE/g. In terms of tyrosinase inhibitory effects, the tested methanol extracts (83.18-89.66 mg KAE/g) were higher than the tested water extracts (18.74-19.11 mg KAE/g). Regarding the BChE inhibitory effects, the methanol extracts were active on the enzyme while the water extracts showed no inhibitory effect on it. Overall, the methanolic extracts showed better enzyme inhibition compared to the infusion extracts. Molecular docking also showed the selected exhibited potential binding affinities with all enzymes, with a preference for cholinesterases. Additionally, the extracts were effective in attenuating the LPS-induced increase in COX-2 and IL-6 gene expression in isolated colon, thus indicating promising anti-inflammatory effects. The preliminary results of this study suggest that these species are good natural sources of antioxidants and also provide some scope as enzyme inhibitors, most likely due to their bioactive contents such as phenolic acids, and thus can be exploited for different applications related to health promotion and disease prevention.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Alcaloides; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); İlaç Keşfi; Kimya (çeşitli); Genel Kimya; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Fizik Bilimleri; Drug Discovery; Chemistry (miscellaneous); General Chemistry; Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; Physical Sciences; Thymbra capitata; Thymus sipyleus subsp; rosulans; phenolic; flavonoid; antioxidant; enzyme inhibitors; anti-inflammatory; ENZYME-INHIBITORY ACTIVITIES; BIOACTIVE COMPOUNDS; MEDICINAL-PLANTS; ANTIOXIDANT; EXTRACTION; PROFILES; POTENT; IDENTIFICATION; POLYPHENOLS; SOLVENT; Thymbra capitata; Thymus sipyleus subsp. rosulans; phenolic; flavonoid; antioxidant; enzyme inhibitors; anti-inflammatory